Multi-document summarization of dissertation abstracts using a variable-based framework - Ou, Shiyan (2010)
This paper reports initial work on developing a method for automatic construction of multi-document summaries of sets of domain-specific dissertation abstracts. A variable-based framework for multi-document summarization of dissertation abstracts in the field of sociology and psychology that makes use of the macro-level and micro-level discourse structure of dissertation abstracts as well as cross-document structure is proposed. The micro-level structure of problem statements found in a sample of 50 dissertation abstracts was analyzed, and the common features found are described. A list of indicator phrases that denote different aspects of the problem statements is provided.